Novice Czech Drivers’ Ability and Willingness to Offer the First Aid after Traffic Accidents: The Positive Effect of the First-Aid Training - Vaclav Linkov; Martina Trepacova; Veronika Kureckova; Chih-Wei Pai (Communications - Scientific letters of the University of Zilina, 2019)
The first aid is an important tool to save people’s lives after traffic accidents. Drivers are the most-likely bystanders, who might help injured people at the traffic accident site. The current research aims to explore Czech learner drivers‘ knowledge and attitudes towards the first aid and to evaluate whether the first aid education increases the likelihood that a driver will provide the first aid for injuries resulting from traffic accidents. A questionnaire survey was conducted in 2015 among a sample of 370 Czech learner drivers at driving schools. The two groups of student drivers were compared - those who had attended the first aid classes (FAC) and those who had not. The learner drivers who had attended an FAC are more likely to know how to treat burns and serious injuries, contain external bleeding, and unblock the respiratory track. Those who had not attended an FAC would more often hesitate to provide the first aid because they resisted taking a leadership role to organize the scene, or they did not have suitable equipment. This supports the idea that increasing the quality of the first aid training for Czech student drivers would improve the traffic safety in the Czech Republic.